Pengembangan Komik Fisika Pada Materi Hukum Newton - Helmiana Dua Meda; Pujianti Bejahida Donuata; Adi Jufriansah (Universitas Hamzanwadi, 2024)
This study aims to find out the feasibility of developing physics comic media on Newton's Law material so that it can be applied to the learning process. The research was conducted at St. Gabriel Maumere Catholic High School Class X MIA which totaled 22 students. According to the findings of the observations, it appears that learning in class still uses teaching materials in the form of books and various facilities such as projectors, LCDs, so most students feel less attractive in the interest in learning. This is due to the fact that educators are less developing learning media, this is a limitation of knowledge. In order to generate a certain product and evaluate its efficacy, a research approach known as research and development (R & D) or research and knowledge (if translated into Indonesian) is employed. Based on the findings of the data analysis, the product was validated by two experts, namely media and material specialists, and received scores of 80% and 91.1% in the 'Very Good' category. Furthermore, the product was tested to 22 students by obtaining 87% results included under the